2021
DOI: 10.1002/tax.12494
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetics of Piresia (Poaceae: Bambusoideae) reveals unexpected generic relationships within Olyreae with taxonomic and biogeographic implications

Abstract: Piresia, a Neotropical herbaceous bamboo genus (Poaceae, Olyreae) including six described species, has a disjunct geographic distribution involving the Caribbean and north/western South America and the northeastern Atlantic Forest in Brazil. Its phylogenetic relationships are poorly known, especially with respect to certain monotypic genera within Olyrinae, such as Reitzia, endemic to the Atlantic forest of southern/south Brazil, and Piresiella, endemic to Cuba. In order to examine the evolutionary history of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 86 publications
(198 reference statements)
0
2
0
Order By: Relevance
“…The earliest diverging, Buergersiochloinae (stem date 42.61 Ma), had, until recently, a single species endemic to the island of New Guinea. Molecular investigations by de Carvalho et al (2021) demonstrated that the Cuban micro‐endemic Piresiella Judz., Zuloaga & Morrone (1 sp., not sampled for this analysis) is sister to Buergersiochloa (1 sp.) and was thus transferred to Buergersiochloinae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The earliest diverging, Buergersiochloinae (stem date 42.61 Ma), had, until recently, a single species endemic to the island of New Guinea. Molecular investigations by de Carvalho et al (2021) demonstrated that the Cuban micro‐endemic Piresiella Judz., Zuloaga & Morrone (1 sp., not sampled for this analysis) is sister to Buergersiochloa (1 sp.) and was thus transferred to Buergersiochloinae.…”
Section: Discussionmentioning
confidence: 99%
“…Sister to Parianinae, the Olyrinae have a crown date of 33.97 Ma. With the transfer of the three endemic Cuban genera to Buergersiochloinae (Lima et al, 2020, 2021), the subtribe is well‐supported as monophyletic in molecular analyses (Ferreira, 2019; de Carvalho, 2021; Oliveira et al, 2020a). The subtribe is Neotropical except for one species of Olyra L. (25 spp.…”
Section: Discussionmentioning
confidence: 99%